Helsesøstres utfordringer for å fremme elevenes psykiske helse - Monica Holm Larsen; Bjørg Christiansen; Lisbeth Gravdal Kvarme (Septentrio Academic Publishing, 2016)
Challenges school nurses have to promote students' mental health The school is an important arena for promoting students' mental health. Prevalence of mental health problems among young people is of concern, and focusing on prevention efforts in schools has been considered to be important. The purpose of this qualitative study was to gain further insight into how collaboration between school nurses and teachers can promote students' mental health. This article is based on four interviews with school nurses from secondary and high school. The school nurses highlighted the importance of establishing themselves as visible partners for teachers, while at the same time providing low threshold for services to students. Factors like lack of time and the location of the school nurse's office, created tension and influenced their work. Much of the work concerning students' mental health was experienced as "fire fighting", while they instead wanted to emphasize health promotion and primary prevention efforts on class and group levels.